Design analysis of the baseplate of a stack module using computer-aided engineering - Iqbal, Muhammad; Puspitasari, Etik (Journal of Engineering and Applied Technology, 2024)
A PWM rectifier is a power converter that functions to convert alternating current into direct current using pulse width modulation (PWM). The baseplate is an important part of the PWM rectifier box, which acts as a stack module holder and has an important role in maintaining the stack module and increasing the power conversion efficiency and reliability of the train traction system. This study aims to determine the effect of variations in material and plate thickness used on Von Mises stress, deformation, and safety factors as well as the mechanical properties of the designed baseplate. The research method used is finite element analysis (FEA) by doing 3D modelling using CAD software and a simulation process using computer-aided engineering (CAE) software with material and plate thickness variations. The results obtained the best baseplate based on the value of Von Mises stress and minimum deformation, as well as the maximum safety factor, namely the baseplate with SS400 material with a plate thickness of 5 mm, with a minimum Von Mises stress value of 76.374 MPa, a minimum deformation value of 0.13611 mm, and a maximum safety factor value of 3.1424. It indicates the effect of material and plate thickness on the value of Von Mises stress, deformation and the resulting safety factor, thus affecting the mechanical properties of a good and safe baseplate in maintaining the performance of the stack module.